Produktivitas Primer Fitoplankton pada Daerah Penangkapan Ikan di Taman Wisata Alam Danau Buyan, Buleleng, Bali - Suardiani, Ni Kadek; Arthana, I Wayan; Kartika, Gde Raka Angga (Current Trends in Aquatic Science; Vol 1 No 1 (2018)DO - 10.24843/CTAS.2018.v01.i01.p02, 2018)
This research aims to identify productivity value of phytoplankton’s net primary as well as its relation within parameter of physics, chemistry, and aquatic biology to the productivity value of phytoplankton’s net primary in the waters of Lake Buyan Nature Park. Measurement of primary phytoplankton productivity is conducted by using bright and dark bottle method.  The taking of lake water samples for measurement of phytoplankton primary productivity and measurement of supporting parameters namely physics (temperature, brightness, turbidity), chemistry (pH, nitrate, phosphate) and biology (phytoplankton abundance) were carried out at four research stations in the fishing area. Data analysis used in this research is correlation analysis among parameters of physic, chemistry, and aquatic biology to the net primary productivity value of phytoplankton by using the PAST 3.1 application. The obtained result showed that the value of net primary productivity ranged from 76.39 to 211.46 mgC / m 3 / day and the parameters of physics, chemistry and aquatic biology have a relationship with net primary productivity of phytoplankton. Brightness, abundance of phytoplankton, nitrate, temperature, dissolved oxygen, pH and phosphate which are positively correlated with net primary productivity of phytoplankton while water turbidity is negatively correlated with it. Parameters that have a strong to very strong relationship with net primary productivity are dissolved oxygen, temperature, nitrate, phytoplankton abundance, and water brightness.